Impact of land use changes to hydrological regime in Nerus Cathment, Terengganu, Malaysia - Mat Nazir, Mohd Hafifi (2016)
Hydrological response in a water catchment area is dominantly received the greatest changes as the impact of changes in land use and magnified by climate influence. The hydrological response can be simplified through expression of Runoff Coefficient (RC) that has been in years of application in the field of hydrology and hydraulic studies. Several current methods applied in this study were covering of rainfall-runoff polygon method and cluster analysis. Both of these methods used for identifying the impact of land use and climate variability on the monthly RC. These methods were able to analyse both the main factor in various verse of interpolations. For modelling purposes, hybrid neural network model was adapted successfully to predict the RC. It was a combination between the time series of RC and neural network. The findings summarize that new method of rainfall-runoff polygon method capable of becoming one of the useful methods with innumerable output exploration which covered a variety of interpretations in the catchment hydrology studies. In addition, the analysis of clusters is suitable to be used as a method of practice in analysing the impact of land use and climate on the hydrological response in a catchment area. Modelling techniques with application of hybrid neural network used in this study able to produce an accurate RC prediction even with the use of restricted hydrological data.